Amino acid and sugar transport in Escherichia coli (ColIb) during abortive infection by bacteriophage T5. - Glenn, J (1979)
T5 bacteriophage cannot replicate in Escherichia coli containing the colicinogenic factor ColIb. We show that active transport of proline and glutamine begins to decline at about 10 min after infection, the same time at which macromolecular synthesis stops during abortive infection. Uptake of alpha-methylglucoside is stimulated, however, and this change is evident even by 5 min after infection. These changes in membrane function do not occur during infections that are productive because of mutations on the plasmid or phage. The results suggest that the abortive infection is caused by membrane depolarization.